Effect of mechanical activation on mullite formation in an alumina-quartz ceramics system - Toplan, H. Özkan (Materiali in tehnologije, 2013)
Powder mixtures of alumina and quartz were being mechanically activated in a planetary mill for 2 h. Both non-activated and activated samples were sintered at different temperatures (1250, 1300, 1325, 1350 and 1375) °C for (1, 2, 3 and 5) h and the formation of a mullite phase was examined with an X-ray diffraction analysis. It was determined that the mechanical activation increased the quantity of the mullite phase.
Keywords: mulit; mullite; mechanical activation; mehanska aktivacija; amorfizacija; amorphization; rentgenska difrakcija; X-ray; diffraction; glinica; kremen; alumina; quartz